Identification of Compounds from the Water Soluble Extract of Cinnamomum cassia Barks and Their Inhibitory Effects against High-Glucose-Induced Mesangial Cells - Qi Luo; Shumei Wang; Qing Lu; Jie Luo; Yong‐Xian Cheng (2013)
The difficulty of diabetic nephropathy (DN) treatment makes prevention the best choice. Cinnamomum cassia barks, known as Chinese cinnamon or Chinese cassia, is one of the most popular natural spices and flavoring agents in many parts of the World. Since previous reports indicated that Chinese cinnamon extract could be used for the treatment of diabetes, we proposed that this spice may be beneficial for the prevention of DN. However, the responsible compounds need to be further identified. In this study, we isolated three new phenolic glycosides, cinnacassosides A-C (1-3), together with fifteen known compounds from the water soluble extract of Chinese cinnamon. The structures of the new compounds were identified by comprehensive spectroscopic evidence. Eleven compounds (6-9, 11, 13-18) were isolated from this spice for the first time, despite extensive research on this species in the past, which added new facets for the chemical profiling of this spice. These isolates were purposely evaluated for their inhibitory effects on IL-6 and extracellular matrix production in mesangial cells which are definitely implicated in DN. The results showed that compounds 4-8 could inhibit over secretion of IL-6, collagen IV and fibronectin against high-glucose-induced mesangial cells at 10 mM, suggesting that Chinese cinnamon could be used as a functional food against DN.